METHODOLOGY FOR FORMATION OF THE OBJECTIVE DATA OF ELECTRONIC STUDENT PORTFOLIO - Roman V. Kron; Ekaterina V. Dolgikh (Moscow Polytechnic University, 2016)
The article describes the approach to the definition of «portfolio», examines the structure and features of an electronic portfolio. The authors give recommendations for students' support in the process of portfolio formation. Rating assessment is used for testing of portfolio effectiveness. We studied realization of this approach based on the integration of the various modules of the AIS «University» applied at Stavropol State Agrarian University.